Comprehensive Analysis of Pyroptosis-Related Genes and Tumor Microenvironment Infiltration Characterization in Papillary Renal Cell Carcinoma - Zhang, Chiyu; Huang, Ruizhen; Xi, Xiaoqing (Frontiers in Molecular Biosciences, 2022)
Background: Immunotherapy has emerged as an important technique for treating a variety of cancers. The dynamic interplay between tumor cells and invading lymphocytes in the tumor microenvironment is responsible for the good response to immunotherapy (TME). Pyroptosis, or inflammation-induced cell death, is closely linked to a number of cancers. However, in papillary renal cell carcinoma (KIRP), the association between pyroptosis and clinical prognosis, immune cell infiltration, and immunotherapy impact remains unknown. Methods: We carefully investigated the link between pyroptosis and tumor growth, prognosis, and immune cell infiltration by evaluating 52 pyroptosis-related genes. The PRG score was utilized to measure a single tumor patient's pyroptosis pattern. After that, we looked at how well these values predicted prognoses and therapy responses in KIRP. Results: We discovered that PRG differences between subgroups were linked to clinical and pathological aspects, prognosis, and TME in two separate genetic subtypes. After that, a PRG score for estimating overall survival (OS) was developed, and its predictive potential in KIRP patients was confirmed. As a result, we developed a very precise nomogram to improve the PRG score's clinical usefulness. A low PRG score, which is determined by mutation load and immune activation, suggess a good chance of survival. Furthermore, the PRG score was linked to chemotherapeutic drug sensitivity in a substantial way. Conclusions: The possible functions of PRGs in the TME, clinical and pathological characteristics, and prognosis were established in our thorough investigation of PRGs in KIRP. These results might help us better understand PRGs in KIRP and offer a new avenue for prognostic evaluation and the development of more effective immunotherapy treatments.